2017
DOI: 10.1590/0102-6720201700010002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Changes in Bowel Habits After Laparoscopic Cholecystectomy

Abstract: Background:The incidence of cholecystolithiasis is approximately 15% of the population. It is believed that between 30-40% of cholecystectomy patients have symptoms after surgery, being changes in bowel habits the most common among them. Aim: 1) Defining the prevalence, and 2) identifying predictors of changes in bowel habits after laparoscopic cholecystectomy. Methods: This is a retrospective cross-sectional study with an initial sample of 150 patients diagnosed with cholecystolithiasis operated between July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Firstly, the small sample size may prevent adequate generalization of results. In addition, the investigated items are extremely subjective and influenced by several factors that may not have been adequately considered despite an appropriate statistical analysis (e.g., the possible influence of previous, concurrent, or subsequent cholecystectomy [ 32 , 33 ]). Finally, a relatively high drop-out rate was recorded in both the compilation of questionnaires and the dosage of vitamin B12, thus potentially hindering a complete rationalization of results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Firstly, the small sample size may prevent adequate generalization of results. In addition, the investigated items are extremely subjective and influenced by several factors that may not have been adequately considered despite an appropriate statistical analysis (e.g., the possible influence of previous, concurrent, or subsequent cholecystectomy [ 32 , 33 ]). Finally, a relatively high drop-out rate was recorded in both the compilation of questionnaires and the dosage of vitamin B12, thus potentially hindering a complete rationalization of results.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Fisher et al 38 concluded that it was associated with being men, younger than 50 and having a high BMI, also confirmed by Yueh et al 39 and Jasim et al 40 (though in this case the age limit was less than 40 years old) while Del Grande et al 35 associated this with prior gastrointestinal symptoms, though they did not define which ones. 35 38–40 Mertens et al clarified this further by stating that it was preoperative flatulence and heartburn which predicted postoperative symptoms including diarrhoea. Yueh et al 39 also found that not following a low-fat diet could be associated with PCD.…”
Section: Discussionmentioning
confidence: 86%
“…33 Thus, it can be seen that the mechanism behind the development of PCD is still not clearly defined despite several avenues being investigated Predictive factors for PCD Predictive factors identified for PCD varied widely across studies that assessed such factors. Fisher et al 38 concluded that it was associated with being men, younger than 50 and having a high BMI, also confirmed by Yueh et al 39 and Jasim et al 40 (though in this case the age limit was less than 40 years old) while Del Grande et al 35 associated this with prior gastrointestinal symptoms, though they did not define which ones. 35 38-40 Mertens et al clarified this further by stating that it was preoperative flatulence and heartburn which predicted postoperative symptoms including diarrhoea.…”
Section: Pathophysiology Of Pcd and Future Work For Understanding The...mentioning
confidence: 86%
See 2 more Smart Citations